Possible selves, vision, and dynamic systems theory in second language learning and teaching - Chan, Hing Yee Letty (2014)
The key purpose of this thesis was to study how vision and possible selves motivate second language (L2) learners in their learning, and the way non-linear and dynamic patterns are exhibited in motivated L2 behaviours. The thesis consists of four studies that investigated the motivation of different target populations (secondary and university learners, and Christian Language Professionals) by using a variety of research methodologies, including retrodictive qualitative modelling (RQM), mixed methods approach, qualitative in-depth interviews and intervention.